A Conceptual Model for Evaluating Digital Intellectual Assets - O. V. Loseva; M. A. Fedotova; N. M. Abdikeev (Финансы: теория и практика, 2023)
The object of the study is the valuation and commercialization of digital intellectual assets. The subject of the study is a conceptual model for assessing the value of digital intellectual assets, reflecting the regulatory framework, objects, subjects, principles, approaches and methods of evaluation involved in civil turnover. The relevance of the study is related to the development of the digital economy and emerging new types of digital assets, including digital intellectual assets, which require their identification and the formation of a theoretical and methodological basis for valuation. The purpose of the study is to build a conceptual model for estimating the value of digital intellectual assets for subsequent commercialization with consideration of the identified identification characteristics, substantiated principles, factors, approaches and methodological tools. The methods of comparative analysis, generalization, classification, logical, semantic and functional modeling, cost estimation are used in the paper. The trends of digitalization of the economy are analyzed, the identification features of digital intellectual assets are determined based on the study of the concepts of “digital asset”, “intellectual asset”, “object of valuation”. A semantic model of the valuation of digital intellectual assets is proposed, illustrating the relationship of its conceptual elements. A process-functional model for estimating the value of digital intellectual assets in IDEF0 notation is constructed. It is concluded that digital intellectual assets as objects of valuation in the conditions of the current regulatory regulation are: 1) the results of intellectual activity created with the use of digital technologies, for which digital rights are fixed in the information system in the form of NFT tokens; 2) digital rights to use intellectual property objects that exist in digital or other forms. Their cost can be determined by the method of analogues, the method of discounted cash flows or the cost of creation method, depending on the purpose of the assessment, the identified factors and taking into account the principles of evaluation.